History and Prehistory of Philosophy:: Some Key Dates - Rossetti, Livio (Revista Archai, 2015)
Philosophy is often taken to be something that is always possible, so that everyone is fully entitled (and no one can avoid) sketching a ‘philosophy’ of his/her own. Nevertheless, it is widely assumed that philosophy began in Miletus with Thales. But it is equally well known that the Presocratics remained unaware of being philosophers, and therefore could not even have wanted to be identified that way. These three points are not mutually compatible. So, what lies behind them? What is escaping our attention when we state them? Probably an event in Plato’s life that has too often gone unnoticed: the key role he played in giving form and substance to philosophy, and in getting it to take root once and for all. Failure to acknowledge how, when, and on whose initiative philosophy came to occupy a very important place in Western culture and education for two and a half millennia; not including a note on this process in biographies of Plato; and overlooking another key event that probably occurred about 350-45 BC - these are just some of the unwelcome effects linked to the usual silence about the period in which philosophy took form.